A Thousand Swings Banua's : Baayun Maulid Tradition as Sustainable Religious Tourism at the Sacred Banua Halat Mosque - Haura Nabila; Rahman Hakim, Arif (Program Studi Sosiologi, FISIP ULM, 2025)
This study examines A Thousand Swings Banua’s: Baayun Maulid Tradition as Sustainable Religious Tourism at the Sacred Banua Halat Mosque. With This study examines